THE ROLE OF SELF-ASSESSMENT IN THE FORMATION OF LONG-TERM STUDENTS TO LOCAL HISTORY WORK - O.V. Bondarenko (Academy of Cognitive and Natural Sciences, 2006)
The article considers the author the main point of appreciating component of the readiness for the local lore work of students. It studies a formedap condition of given structural element.